Knowledge, attitude and practice on carbonated drinks consumption among young adults in Pekan, Pahang - Mohamad Zailani, Nurfarzana; Hamirudin, Aliza Haslinda (2019)
Background: Consumption of carbonated drinks among young adults increases due to variety of carbonated drinks available in the markets. This situation can put health condition of young adults at risk which may expose them to non-communicable disease such as diabetes. Purpose: This study aimed at assessing knowledge, attitude and practice (KAP) on carbonated drinks consumption among young adults in Pekan, Pahang. A comparison between young adults males and females on knowledge, attitude and practice of carbonated drinks intake was studied. Methodology: A total of 94 respondents consist of 47 males and 47 females aged 18 to 35 years old participated in this study. The KAP questionnaires were distributed to various housing area around Pekan, Pahang. Data analysis involved descriptive statistics, Independent T-test (parametric test) and Mann-Whitney U test (non-parametric test). P-value was set at p<0.05 as statistically significant. Results: Result obtained for knowledge showed that there was no significant difference in knowledge score in percentage between males and females (p=0.831). It indicated that there was no difference among males and females regarding knowledge and understanding level on carbonated drinks. Meanwhile, there were significant differences for both attitude (p=0.049) and practice (p=0.032) score in percentage between males and females. This study demonstrated that males have negative attitude and high practice on consumption of carbonated drinks compared to females. Conclusion: In conclusion, an awareness program is required to be implemented in this population in order to reduce the consumption of carbonated drinks as it can lead to adverse health effects. Besides, involvement from various agencies which include health professionals and media are important in order to make the community aware about the importance of good nutritional status and health.